PET tracers in glioblastoma: Toward neurotheranostics as an individualized medicine approach - Dadgar, Habibullah; Jokar, Narges; Nemati, Reza; Larvie, Mykol; Assadi, Majid (Frontiers in Nuclear Medicine, 2023)
Over the past decade, theragnostic radiopharmaceuticals have been used in nuclear medicine for both diagnosis and treatment of various tumors. In this review, we carried out a literature search to investigate and explain the role of radiotracers in the theragnostic approach to glioblastoma multiform (GBM). We primarily focused on basic and rather common positron emotion tomography (PET) radiotracers in these tumors. Subsequently, we introduced and evaluated the preclinical and clinical results of theranostic-based biomarkers including integrin receptor family, prostate-specific membrane antigen (PSMA), fibroblast activated protein (FAP), somatostatin receptors (SRS), and chemokine receptor-4 (CXCR4) for patients with GBM to confer the benefit of personalized therapy. Moreover, promising research opportunities that could have a profound impact on the treatment of GBM over the next decade are also highlighted. Preliminary results showed the potential feasibility of the theragnostic approach using theses biomarkers in GBM patients.